Association of calcium supplement with risk of incident arrhythmia - Ru Chen; Duqiu Liu; Chenxing Yang; Tianyu Guo; Sen Liu; Yi Guo; Jinjie Xiong; Shan Deng (The Journal of Nutrition, Health and Aging, 2025)
Background and aims: Calcium plays a crucial role in cardiac electrophysiology, but the association between calcium supplement and the risk of incident arrhythmia remains unclear. Objective: To investigate the relationship between habitual calcium supplement and incident risk of cardiac arrhythmia. Methods: We conducted a prospective study of 480,972 participants from the UK Biobank. Habitual calcium supplement was treated as the main exposure. The primary outcome was the incidence of arrhythmias, including atrial fibrillation/flutter (AF/AFL), ventricular arrhythmia (VA), and bradyarrhythmia. Cox proportional hazards regression models were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs). Results: After a median follow-up of 11.69 years, 46,609 incident arrhythmia cases were documented, including 36,406 AF/AFL, 5,370 VA, and 14,226 bradyarrhythmia. After multivariable adjustment, calcium supplement was associated with an increased risk of total arrhythmias (HR 1.11, 95% CI 1.05–1.19), AF/AFL (HR 1.20, 95% CI 1.12–1.28), VA (HR 1.14, 95% CI 1.07–1.21), and bradyarrhythmia (HR 1.18, 95% CI 1.11–1.26). Significant interactions were observed between calcium supplement and estimated glomerular filtration rate, diabetes, cardiovascular disease, and polygenic risk score for AF (all p for interaction < 0.05). Conclusions: Calcium supplement was associated with an increased risk of incident arrhythmia. Careful evaluation of the potential arrhythmic risk is warranted when considering calcium supplement in individuals with clinical indications.